The Effect of Social Support on Employee Burnout: A Leadership Style Perspective - Nisa, Nur Ifani Chaerun; Salim, Agus (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
This study aims to examine the effect of social support on employee burnout from the perspective of leadership style. This study employed quantitative approach and used a questionnaire to collect data from 100 employees working in Jakarta, selected through incidental sampling. The measurement tools in this study included the burnout scale, social support scale, and leadership style scale. Data were analyzed using ANCOVA with the assistance of SPSS version 25 for Windows. The results indicate a significant effect of social support on burnout when viewed through the lens of leadership style, with a significance value of 0.008 (p < 0.05). In addition, minor hypothesis testing revealed a significant relationship between social support and burnout, with a significance value of 0.000. However, the relationship between burnout and leadership style was close to significance, with a value of 0.054, while the relationship between social support and leadership style was not significant, with a significance value of 0.182. These findings suggest that social support plays a crucial role in reducing burnout, while leadership style influences the effectiveness of that support. This study provides practical implications for organizations by emphasizing the importance of fostering social support to mitigate employee burnout and promoting leadership styles that enhance employee well-being. Penelitian ini bertujuan untuk menguji pengaruh dukungan sosial terhadapp burnout karyawan yang ditinjau dari gaya kepemimpinan. Penelitian ini menggunakan pendekatan kuantitatif dengan metode kuisioner terhadap 100 karyawan yang bekerja di Jakarta yang dipilih dengan menggunakan metode sampling incidental. Alat ukur yang digunakan dalam penelitian ini meliputi skala burnout, skala dukungan sosial, dan skala gaya kepemimpinan. Penelitian ini menggunakan analisis ANCOVA dengan bantuan SPSS versi 25 for windows. Hasil penelitian menunjukkan adanya pengaruh yang signifikan antara dukungan sosial terhadap burnout ditinjau dari gaya kepemimpinan dengan nilai signifikansi 0,008 (p